THE VIOLENT REVERIE: THE UNCONSCIOUS IN LITERATURE AND SOCIETY - Manganyi, N Chabani (PINS-Psychology in Society, 2025)
If we substitute Erikson’s nomination of the notions of relativity and the unconscious as two insights which provided “disturbing extensions of human consciousness in our time” with tyranny and militant terrorism we introduce an immediate shift from the realm of ideas to that of raw everyday experience.1 Militant terrorism and institutionalised tyranny constitute some of the raw experience of man in contemporary societies.